35th AIAA Applied Aerodynamics Conference 2017
DOI: 10.2514/6.2017-3752
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Multimodality in Aerodynamic Shape Optimization Based on the Reynolds Averaged Navier-Stokes Equations

Abstract: This paper presents an improvement to a multi-start method for gradient based exploration of moderately multimodal design spaces in aerodynamic shape optimization problems. Free form deformation geometry control is used in conjunction with a gradient-based multistart algorithm to generalize cascading linear constraints for a sampler algorithm into a geometry-independent form. This permits large, high-quality, feasible samples of the design space to be generated and optimized quickly and e ciently. This algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…Wings in various flow regimes are designed with ease and are now simple enough to be considered as academic base cases [1,6,53,20,26]. Aircraft configurations may be studied through multidisciplinary design optimization that takes into account both the flow and the structure [45,28,24].…”
Section: Numerical Optimizationmentioning
confidence: 99%
“…Wings in various flow regimes are designed with ease and are now simple enough to be considered as academic base cases [1,6,53,20,26]. Aircraft configurations may be studied through multidisciplinary design optimization that takes into account both the flow and the structure [45,28,24].…”
Section: Numerical Optimizationmentioning
confidence: 99%
“…For aerofoil optimization, it has been suggested that ASO problems exist that are unimodal [30] and multimodal [31,32], while the same is true of wings exhibiting unimodality [33] and multimodality [30]. Recently, results of the optimization of a rectangular wing in inviscid subcritical flow (this is case 6 of the AIAA ADODG [34]) have been presented investigating the degree of multimodality in that case [35][36][37][38]. However, while some aerodynamic optimization problems are multimodal, there is little effort to attempt to identify and characterise these.…”
Section: Introductionmentioning
confidence: 99%
“…Similar approaches were performed by Bons at al. [36], and Streuber and Zingg [38]. The current authors performed similar work by running a heuristic global optimizer multiple times on the same problem to analyse whether it converged to different solutions each time [37].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 It has been demonstrated that multimodality can exist in aerodynamic shape optimization problems, 11 and the importance of understanding multimodality in this context is underscored by the recent inclusion of a multimodal problem in the Aerodynamic Design and Optimization Discussion Group (ADODG) test suite at the AIAA Aviation 2017 conference. [12][13][14][15] The objective of this paper is to present a detailed study of the relationship between various problem parameters and multimodality in aerodynamic shape optimization of wings. This includes variations in available degrees of freedom, constraints, as well as Mach number, with particular attention paid to di↵erences ⇤ Ph.D.…”
Section: Introductionmentioning
confidence: 99%
“…On the other end of the spectrum, the existence of multimodality in the aerodynamic shape optimization of a wing in general is demonstrated in several previous works. 11,15,21 Between these extremes must lie a region in which multimodality changes from significant to insignificant and it is a goal of this work to determine the boundaries of these regions within the design space. This is accomplished by utilizing the free-form deformation 22 (FFD) based gradient-based multistart (GBMS) algorithm the authors published previously 15 to thoroughly explore the design space, specifically addressing the causes and extent of multimodality in the optimization of an aircraft wing under varying degrees of freedom, constraints, and operating conditions.…”
Section: Introductionmentioning
confidence: 99%